Catalyst for acetylene dimerization reaction as well as preparation method and application thereof
By using the catalyst prepared by CuCl2, NEP and coconut shell activated carbon, the problems of short life, high cost and low selectivity in the acetylene dimerization reaction are solved, and efficient and stable vinyl acetylene production is achieved.
Patent Information
- Application Number
- CN202411632260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-21
AI Technical Summary
In the acetylene dimerization reaction, existing catalysts have problems such as short life, high production cost, acetylene conversion rate and low vinyl acetylene selectivity.
CuCl2 is used as the main catalyst, 1-ethyl-2-pyrrolidone (NEP) is used as the ligand, and coconut shell activated carbon is used as the support to prepare the catalyst through a specific preparation method to improve catalytic activity and stability.
It significantly improves the conversion rate of acetylene and the selectivity of vinyl acetylene, extends the life of the catalyst, reduces production costs, and improves production efficiency.
Smart Images

Figure CN119488955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalyst for acetylene dimerization reaction and a preparation method and application thereof. Background Art
[0002] The preparation of vinyl acetylene by acetylene dimerization is an important operating unit in the production of chloroprene rubber by the acetylene process. At the same time, vinyl acetylene can be used in the production of chemical products such as benzene, diacetyl, 4-chlorophthalic anhydride and vinyl polymers, as well as the production of many traditional petrochemical products, which can effectively alleviate the current industrial production's dependence on the petrochemical industry. Therefore, the efficient production of vinyl acetylene is of great significance.
[0003] At present, vinyl acetylene is mainly produced through the acetylene dimerization reaction with the participation of catalysts. Among them, the acetylene conversion rate of the catalyst, the vinyl acetylene selectivity and the stability of the catalyst are crucial. In previous studies, a highly efficient Cu-DMF / AC catalyst with a Cu-O coordination structure was reported, which showed the best catalytic performance in the gas-solid acetylene dimerization reaction. The introduction of N,N-dimethylformamide (DMF) ligand changed the electronic environment, enhanced the reducibility of Cu(II), and improved the dispersion of active metals. At the same time, the active center Cu(DMF) in the Cu-DMF / AC catalyst 2 Cl 2 The increase in steric hindrance of the complex can effectively inhibit the formation of the byproduct DVA and significantly improve the catalyst selectivity. However, these catalysts have disadvantages such as short lifespan.
[0004] In view of this, the present invention proposes a new catalyst for acetylene dimerization reaction and a preparation method thereof. The catalyst can be effectively used in acetylene dimerization reaction, has strong stability, can reduce production costs, improve production efficiency, and can further efficiently prepare vinyl acetylene and be effectively applied to large-scale industrial production. Summary of the invention
[0005] The purpose of the present invention is to provide a catalyst for acetylene dimerization reaction, which has strong acetylene activation ability, high acetylene conversion rate and vinyl acetylene selectivity, so that the acetylene dimerization reaction involving the catalyst can efficiently produce vinyl acetylene, and has the advantages of high catalytic activity and cheap materials.
[0006] In order to achieve the above purpose, the technical solution adopted is:
[0007] A catalyst for acetylene dimerization reaction, comprising: a main catalyst, a ligand, and a carrier;
[0008] The main catalyst is cupric chloride; the ligand is 1-ethyl-2-pyrrolidone; and the carrier is coconut shell activated carbon.
[0009] Furthermore, the molar ratio of the main catalyst to the ligand is 1:0.5-2.
[0010] Furthermore, the mass ratio of the copper element to the carrier in the main catalyst is 5-20:100.
[0011] Furthermore, the coconut shell activated carbon is 60-80 mesh coconut shell activated carbon.
[0012] Another object of the present invention is to provide a method for preparing the above-mentioned catalyst, which is simple.
[0013] In order to achieve the above purpose, the technical solution adopted is:
[0014] The preparation method of the above catalyst comprises the following steps:
[0015] (1) After the main catalyst is completely dissolved in water, the ligand is added dropwise at 20-50°C and stirred to allow it to fully coordinate to obtain a complex solution;
[0016] (2) adding a carrier to the complex solution, stirring to load the complex on the carrier, and drying to obtain the catalyst.
[0017] Furthermore, in the step (1), stirring is performed for 20-40 minutes to allow the main catalyst and the ligand to be fully coordinated.
[0018] Furthermore, in the step (2), the drying process is: drying at 60-90°C for 4-12h, and then drying at 90-120°C for 4-12h.
[0019] Furthermore, in the steps (1) and (2), the stirring speed is 300-700 rpm.
[0020] Another object of the present invention is to provide the use of the above catalyst.
[0021] The application of the above catalyst in the acetylene dimerization reaction is: adding the above catalyst into a reactor, and then introducing acetylene into the reactor to cause a dimerization reaction to generate vinyl acetylene.
[0022] Furthermore, the reaction temperature in the reactor is 90-110°C, and the acetylene space velocity is 100-140h -1 .
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. In the technical solution of the present invention, the added NEP and copper form a coordination structure, which changes the electronic environment, enhances the reducibility of Cu(II) species, and shortens the activation time of the reaction.
[0025] 2. In the technical solution of the present invention, as the chain length of the alkyl substituent on the nitrogen atom of 2-pyrrolidone increases, the electron donating ability of the ligand is enhanced, the coordination number and bond length of the Cu-O bond in the Cu-based ligand catalyst are reduced, and the number of low-coordinated Cu sites is increased.
[0026] 3. In the technical solution of the present invention, the addition of NEP makes the entire catalytic system more stable and has higher catalytic activity. The conversion rate of acetylene, the single-pass yield and selectivity of vinyl acetylene are significantly improved.
[0027] 4. In the technical solution of the present invention, the interaction between copper and NEP ligands reduces the energy barrier of acetylene dimerization to generate MVA and enhances the energy barrier of secondary reaction to generate DVA. Therefore, the addition of NEP inhibits the formation of polymers and avoids the situation where the polymer blocks the gas path.
[0028] 5. In the technical solution of the present invention, the NEP ligand can inhibit the loss and agglomeration of the active component Cu species during the catalytic reaction and improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The performance of the catalyst prepared in the implementation case in catalyzing the dimerization of acetylene;
[0030] Figure 2 FT-IR characterization of the catalyst prepared in the implementation case;
[0031] Figure 3 XRD characterization of the catalyst prepared in the implementation case;
[0032] Figure 4 is the H of the catalyst prepared in the implementation case 2 -TPR characterization;
[0033] Figure 5 TG and DTG characterization of the catalyst prepared in the implementation case.
[0034] Figure 6 TEM characterization of the catalyst prepared in the implementation case;
[0035] Figure 7 XPS characterization of the catalyst prepared in the implementation case. DETAILED DESCRIPTION
[0036] In order to further explain the catalyst for acetylene dimerization reaction and its preparation method and application of the present invention and achieve the intended purpose of the invention, the catalyst for acetylene dimerization reaction and its preparation method and application, its specific implementation method, structure, characteristics and efficacy proposed by the present invention are described in detail below in combination with preferred embodiments. In the following description, different "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0037] The following will further introduce in detail the catalyst for acetylene dimerization reaction and its preparation method and application in conjunction with specific embodiments:
[0038] In order to overcome the problems of complex process, high production cost, low single-pass conversion rate of acetylene and low selectivity of vinyl acetylene in the prior art of acetylene dimerization, the present invention provides a catalyst for acetylene dimerization reaction and its preparation method and application. According to the technical solution of the present invention, the catalyst adopts CuCl 2 ·2H 2 O is the main catalyst, 1-ethyl-2-pyrrolidone (NEP) is the ligand, deionized water is the solvent, and coconut shell activated carbon is the carrier. The gas-solid acetylene dimerization catalyst according to the embodiment of the present invention has a strong activation ability for acetylene, a high acetylene conversion rate and a high selectivity for vinyl acetylene, so that the acetylene dimerization reaction in which the catalyst participates can efficiently produce vinyl acetylene. According to a specific example of the present invention, the gas-solid acetylene dimerization catalyst of the present invention can be effectively used for acetylene dimerization, reduce production costs, and improve production efficiency, and thus can efficiently prepare vinyl acetylene and be effectively applied to large-scale industrial production.
[0039] The technical solution of the present invention is:
[0040] A catalyst for acetylene dimerization reaction, comprising: a main catalyst, a ligand, and a carrier;
[0041] The main catalyst is cupric chloride; the ligand is 1-ethyl-2-pyrrolidone; and the carrier is coconut shell activated carbon.
[0042] Preferably, the molar ratio of the main catalyst to the ligand is 1:0.5-2.
[0043] Preferably, the mass ratio of the copper element to the carrier in the main catalyst is 5-20:100.
[0044] Preferably, the coconut shell activated carbon is 60-80 mesh coconut shell activated carbon.
[0045] The preparation method of the above catalyst comprises the following steps:
[0046] (1) After the main catalyst is completely dissolved in water, the ligand is added dropwise at 20-50°C and stirred to allow it to fully coordinate to obtain a complex solution;
[0047] (2) adding a carrier to the complex solution, stirring to load the complex on the carrier, and drying to obtain the catalyst.
[0048] Preferably, in step (1), stirring is performed for 20-40 minutes to allow the main catalyst and the ligand to be fully coordinated.
[0049] Preferably, in the step (2), the drying process is: drying at 60-90°C for 4-12h, and then drying at 90-120°C for 4-12h.
[0050] Preferably, in steps (1) and (2), the stirring speed is 300-700 rpm.
[0051] The application of the above catalyst in the acetylene dimerization reaction is: adding the above catalyst into a reactor, and then introducing acetylene into the reactor to cause a dimerization reaction to generate vinyl acetylene.
[0052] Preferably, the reaction temperature in the reactor is 90-110°C, and the acetylene space velocity is 100-140h -1 .
[0053] In order to improve the selectivity and stability of Cu-based ligand catalysts in the gas-solid phase acetylene dimerization catalytic system, it is possible to consider screening ligands with the same amide functional group as DMF, obvious steric hindrance and higher flash point.
[0054] Pyrrolidone ligands derived from 2-pyrrolidone have obvious spatial and electronic properties, which are superior to traditional amide compounds. Different substituents on the nitrogen atom have different effects on 2-pyrrolidone, resulting in its diverse electronic and spatial steric effects. In Cu-based ligand catalysts, alkyl substituents with different chain lengths on 2-pyrrolidone ligands affect both the electronic properties of the Cu active center and its spatial characteristics. In addition, 2-pyrrolidone and its derivatives have amide functional groups and high flash points. The flash point of 2-pyrrolidone is 129.9℃, which is higher than the temperature of gas-solid acetylene dimerization reaction (100℃). Therefore, combining the good advantages of 2-pyrrolidone ligands and Cu, it is of great significance to design Cu-based ligand catalysts with high selectivity and stability for application in gas-solid acetylene dimerization catalytic systems.
[0055] Based on this, in order to overcome the limitations of the stability of the Cu-DMF catalyst in the gas-solid acetylene dimerization reaction, which is mainly manifested in the loss of the active component Cu species and the escape of the DMF ligand. The present invention selects 2-pyrrolidone and its derivatives having the same amide functional group as DMF and a higher flash point as ligands to prepare a Cu-based catalyst catalytic gas-solid acetylene dimerization catalytic system. At the same time, by adjusting the different chain lengths of the alkyl substituents on the nitrogen atom of the 2-pyrrolidone ligand, the electronic properties and steric hindrance of the active center of the Cu-based catalyst are regulated to explore the influence of electronic and steric effects on the performance of the Cu-based catalyst. The specific embodiments are as follows:
[0056] Example 1.
[0057] The synthesis of supported Cu / AC catalyst, the specific steps are as follows:
[0058] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0059] 4 g of coconut shell activated carbon (60-80 mesh) was added, and then stirred overnight. The resulting mixture was dried in a drying oven at 80° C. for 12 h, and then the temperature of the constant temperature drying oven was increased to 100° C. and continued to be dried for 12 h. After cooling, the catalyst was obtained. The solid catalyst was denoted as Cu / AC.
[0060] Example 2.
[0061] The synthesis of supported NEP / AC catalyst, the specific steps are as follows:
[0062] 10 mL of deionized water was added to the beaker with the magnet, and the stirrer thermostat system was adjusted to 30° C. and the stirring rate was 400 rpm.
[0063] 1-Ethyl-2-pyrrolidone (NEP) was added dropwise into the beaker and stirred for 30 minutes. 4 g of coconut shell activated carbon (60-80 mesh) was added and stirred overnight. The resulting mixture was dried in a drying oven at 80° C. for 12 hours. The temperature of the constant temperature drying oven was then increased to 100° C. and continued to be dried for 12 hours. The catalyst was obtained after cooling. The solid catalyst was denoted as NEP / AC.
[0064] Example 3.
[0065] The synthesis of supported Cu-L1 / AC catalyst, the specific steps are as follows:
[0066] 1.47 g of CuCl 2 ·2H 2O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0067] 2-Pyrrolidone (L1) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 2-pyrrolidone to fully coordinate. 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0068] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-L1 / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0069] Example 4.
[0070] The synthesis of supported Cu-L2 / AC catalyst, the specific steps are as follows:
[0071] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0072] 1-Methyl-2-pyrrolidone (L2) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-methyl-2-pyrrolidone to fully coordinate. 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0073] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-L2 / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0074] Example 5.
[0075] The synthesis of supported Cu-L3 / AC catalyst, the specific steps are as follows:
[0076] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0077] 1-Ethyl-2-pyrrolidone (L3) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-ethyl-2-pyrrolidone (L3) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0078] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-5DMF / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0079] Example 6.
[0080] The synthesis of supported Cu-L4 / AC catalyst, the specific steps are as follows:
[0081] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0082] 1-propyl-2-pyrrolidone (L4) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-propyl-2-pyrrolidone (L4) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0083] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-L4 / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0084] Example 7.
[0085] The synthesis of supported Cu-L5 / AC catalyst, the specific steps are as follows:
[0086] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0087] 1-Butyl-2-pyrrolidone (L5) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-butyl-2-pyrrolidone (L5) to fully coordinate. 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0088] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-L5 / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0089] Example 8.
[0090] The synthesis of supported Cu-L6 / AC catalyst, the specific steps are as follows:
[0091] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0092] Polyvinyl pyrrolidone (L6) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and polyvinyl pyrrolidone (L6) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0093] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-L6 / AC (the molar ratio of the main catalyst and the ligand was 1:1).
[0094] Example 9.
[0095] The synthesis of supported Cu-0.5NEP / AC catalyst, the specific steps are as follows:
[0096] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0097] 1-Ethyl-2-pyrrolidone (NEP) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-ethyl-2-pyrrolidone (NEP) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0098] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-0.75NEP / AC (the molar ratio of the main catalyst and the ligand was 1:0.5).
[0099] Example 10.
[0100] The synthesis of supported Cu-0.75NEP / AC catalyst, the specific steps are as follows:
[0101] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0102] 1-Ethyl-2-pyrrolidone (NEP) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-ethyl-2-pyrrolidone (NEP) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0103] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-1.25NEP / AC (the molar ratio of the main catalyst and the ligand was 1:0.75).
[0104] Example 11.
[0105] The synthesis of supported Cu-1.25NEP / AC catalyst, the specific steps are as follows:
[0106] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0107] 1-Ethyl-2-pyrrolidone (NEP) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-ethyl-2-pyrrolidone (NEP) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0108] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-1.25NEP / AC (the molar ratio of the main catalyst and the ligand was 1:1.25).
[0109] Example 12.
[0110] The synthesis of supported Cu-2NEP / AC catalyst, the specific steps are as follows:
[0111] 1.47 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 30 °C and the stirring rate to 400 rpm to fully dissolve the cupric chloride.
[0112] 1-Ethyl-2-pyrrolidone (NEP) was added dropwise to the beaker, and the mixture was stirred at 400 rpm for 30 min to allow copper chloride and 1-ethyl-2-pyrrolidone (NEP) to fully coordinate, and 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 400 rpm overnight.
[0113] The obtained mixture was dried in a drying oven at 80°C for 12 hours, and then the temperature of the constant temperature drying oven was increased to 100°C and continued to be dried for 12 hours. After cooling, the catalyst was obtained. The solid catalyst was represented by Cu-1.25NEP / AC (the molar ratio of the main catalyst and the ligand was 1:2).
[0114] Example 13.
[0115] The specific steps are as follows:
[0116] (1) Synthesis of supported Cu-NEP / AC catalyst,
[0117] 0.54 g of CuCl 2 ·2H 2 O and 10 mL of deionized water were added into the beaker with a magnet, and the constant temperature system of the stirrer was adjusted to 20 °C and the stirring rate to 700 rpm to fully dissolve the cupric chloride.
[0118] 1-Ethyl-2-pyrrolidone was added dropwise to the beaker, and the mixture was stirred at 700 rpm and 20°C for 40 min to allow the copper chloride and 1-ethyl-2-pyrrolidone to fully coordinate. 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 700 rpm and 20°C overnight.
[0119] The obtained mixture was dried in a drying oven at 90°C for 4 h, then the temperature of the constant temperature drying oven was increased to 120°C and continued to be dried for 4 h. After cooling, a solid catalyst table (the molar ratio of the main catalyst to the ligand was 1:1) was obtained.
[0120] (2) After adding 2 mL (1.2 g) of the solid catalyst prepared in step (1) into the reactor, acetylene was introduced, the reaction temperature was 110° C., the reaction pressure was normal pressure, and the acetylene space velocity was 100 h -1 Acetylene undergoes dimerization over the Cu-NEP / AC catalyst to produce vinyl acetylene.
[0121] Example 14.
[0122] The specific steps are as follows:
[0123] (1) Synthesis of supported Cu-NEP / AC catalyst,
[0124] 2.15 g of CuCl 2 ·2H 2 O and 20 mL of deionized water were added into the beaker with a magnet, and the stirrer thermostat system was adjusted to 50 °C and the stirring rate to 300 rpm to fully dissolve the cupric chloride.
[0125] 1-Ethyl-2-pyrrolidone was added dropwise to the beaker, and the mixture was stirred at 300 rpm and 50° C. for 20 min to allow copper chloride and 1-ethyl-2-pyrrolidone to fully coordinate. 4 g of coconut shell activated carbon (60-80 mesh) was added, and the mixture was stirred at 300 rpm and 50° C. overnight.
[0126] The obtained mixture was dried in a drying oven at 60°C for 11 h, and then the temperature of the constant temperature drying oven was increased to 90°C for further drying for 11 h. After cooling, a solid catalyst (the molar ratio of the main catalyst to the ligand was 1:1) was obtained.
[0127] (2) After adding 2 mL (1.2 g) of the solid catalyst prepared in step (1) into the reactor, acetylene was introduced, the reaction temperature was 90° C., the reaction pressure was normal pressure, and the acetylene space velocity was 140 h -1 Acetylene dimerizes over the Cu-NEP / AC catalyst to produce vinyl acetylene.
[0128] Example 15.
[0129] The specific steps are as follows:
[0130] The method is as follows: in a fixed bed microreactor device, the catalyst prepared in Example 1-12 is used to carry out acetylene dimerization reaction. 2 mL (1.2 g) of the copper-based catalyst is taken into the acetylene dimerization reaction device to carry out gas-solid acetylene dimerization reaction. The reaction conditions are as follows: reaction temperature 100°C, reaction pressure normal pressure, acetylene space velocity 120 h -1 .
[0131] Finally, the gas mixture was injected into a gas chromatograph (Shimadzu, GC-2014C, GDX-301 and flame ionization detector) every 20 minutes during the experiment to analyze its composition. The products obtained from the acetylene dimerization reaction were quantitatively analyzed using the calibrated area normalization method. The conversion rate of acetylene (X) and the selectivity of MVA (S) are used to evaluate the performance of copper-based catalysts in the catalytic acetylene dimerization reaction. The main product of the acetylene dimerization gas-solid catalytic system is MVA, and the by-products are DVA and 2-chloro-1,3-butadiene, etc., as well as acetylene that does not participate in the reaction. The conversion rate of acetylene and the selectivity of MVA are calculated as follows:
[0132] X=[(2α 2 +2α 3 +3α 4 ) / (α 1 +2α 2 +2α 3 +3α 4 )×100%
[0133] S = [2α 2 / (α 1 +2α 2 +2α 3 +3α 4 )×100%
[0134] Among them, α1, α2, α3, and α4 are the C 2 H 2 , MVA, 2-chloro-1,3-butadiene, 1,5-hexadiene-3-yne (DVA) volume fraction. The amount of reactants in the product is measured by the level of X. 2 H 2 The higher the conversion rate, the higher the C 2 H 2 The consumption is large. S is a measure of the amount of the target product MVA generated. The higher the selectivity of MVA, the more MVA is generated in the reaction.
[0135] (1) Investigate the effects of different ligands on catalysts
[0136] Six pyrrolidone ligands were selected as the research objects: 2-pyrrolidone (L1), 1-methyl-2-pyrrolidone (L2), 1-ethyl-2-pyrrolidone (L3), 1-propyl-2-pyrrolidone (L4), 1-butyl-2-pyrrolidone (L5) and polyvinylpyrrolidone (L6) (the structures of pyrrolidone ligands are shown in Figure 1 (a)), the effects of different chain lengths of alkyl substituents on the nitrogen atom of 2-pyrrolidone on the gas-solid acetylene dimerization performance were studied.
[0137] The results are as follows Figure 1 As shown in Figure 2, the catalytic activity of Cu / AC catalysts was significantly improved by introducing pyrrolidone ligands with different chain length substituents into the catalyst. Figure 1 As shown in (b)-1(d), the order of acetylene conversion is Cu-L1 / AC>Cu-L2 / AC>Cu-L3 / AC>Cu-L4 / AC>Cu-L5 / AC>Cu-L6 / AC, and the numerical order of MVA selectivity is Cu-L3 / AC>Cu-L4 / AC>Cu-L2 / AC>Cu-L5 / AC>Cu-L1 / AC>Cu-L6 / AC. According to the results of MVA yield, the ligand can be arranged in the following order to improve the catalytic performance of Cu-based catalysts: L3>L2>L1>L4>L5>L6. The performance test results show that when the substituent on the nitrogen atom of 2-pyrrolidone is ethyl, that is, the ligand is 1-ethyl-2-pyrrolidone (NEP), the catalyst exhibits the best catalytic performance. Therefore, it is speculated that the structure of the pyrrolidone-based ligand will affect the electronic properties and active center of the active center Cu in the catalyst.
[0138] (2) Investigate the effect of different NEP / Cu molar ratios on the catalyst
[0139] The method (1) was used to carry out acetylene dimerization reaction on the catalysts of Examples 1, 5, 9-12, and the performance of the catalysts was measured to explore the relationship between the performance of the Cu-NEP / AC catalyst and the NEP / Cu molar ratio.
[0140] The results are as follows Figure 1 As shown in (e) and 1(f), with the increase of NEP / Cu molar ratio, the conversion rate of acetylene increases first and then decreases. When the molar ratio of Cu: NEP ligand is 1:0.75, the Cu-0.75NEP / AC catalyst has the best catalytic performance. 2 H 2The conversion rate was 65% and the MVA selectivity was 85%. The catalytic performance of Cu-0.75NEP / AC and Cu / AC catalysts was compared under the same conditions. The results showed that the acetylene conversion rate of Cu-0.75NEP / AC catalyst was 65% at the beginning of the reaction, which dropped to 55% after 20 hours; while the acetylene conversion rate of Cu / AC catalyst was only 25% at the beginning of the reaction, which dropped to 6.4% after 20 hours. This shows that the conversion rate of Cu / AC catalyst can be increased by about 40% by introducing NEP ligand modification.
[0141] Example 16.
[0142] The catalysts prepared in the examples of the present invention were subjected to various characterization tests.
[0143] The information related to the catalyst surface functional groups was obtained by Fourier transform infrared spectrometer (Thermo Fisher Scientific, Waltham, USA) using KBr as diluent.
[0144] A deep understanding of the initial configuration of the active catalyst is the key to exploring the reaction mechanism. In order to confirm the role of the ligand in the Cu-based catalyst, a series of 2-pyrrolidone ligands (L1, L2, L3, L4, L5 and L6) were studied by FT-IR spectroscopy with CuCl 2 interaction. Figure 2 CuCl 2 , Lx (L1, L2, L3, L4, L5 and L6) ligands and CuCl 2 - FT-IR spectra of Lx (L1, L2, L3, L4, L5 and L6) samples. CuCl 2 , Lx (L1, L2, L3, L4, L5 and L6) ligands and CuCl 2 -The spectra of Lx (L1, L2, L3, L4, L5 and L6) samples are obviously different. Figure 2 As shown in (c), in the Cu-L3 sample, the -1 The peak at 1633 cm -1 CuCl 2 -L3's C=O stretching vibration, compared to NEP, CuCl 2 - The C=O stretching vibration of L3 occurred at 40 cm -1 The results confirmed the formation of Cu-NEP complexes. Similar C=O stretching vibration shifts were also observed in other catalysts, indicating that the Cu of the Cu-based catalysts can coordinate with the pyrrolidone ligands to form Cu-(L1, L2, L3, L4, L5 and L6) complexes.
[0145] Example 17.
[0146] X-ray photoelectron spectroscopy (XPS) was used to analyze the valence state and electronic structure characteristics of the elements in the catalyst, and to semi-quantitatively analyze the elemental composition on the catalyst surface. XPS analysis was performed using a Thermo ESCALAB250XI spectrometer equipped with a monochromatic Al-Kα X-ray source with an optical power of 225 W. The detection results were calibrated based on the C1s peak (284.6 eV). Thermo vantage software was used to determine the elemental composition based on the peak area and sensitivity coefficient of the C1s, N 1s, O 1s, and Cu 2p peaks.
[0147] In order to explore the valence change of Cu species in the Cu-based catalyst and the interaction between Cu species and pyrrolidone ligands, XPS spectra and Auger spectroscopy were performed on the catalysts of Examples 1 and 3-8 before and after the reaction (the reaction was carried out using the method of Example 13). Figure 3 As shown in the figure, the peak of 932-935.5eV is divided into two peaks by curve fitting. The first main peak is located at around 934.8eV, while the second small peak is located at around 932.8eV. The higher energy main peak (934.7eV) can be attributed to the characteristic peak of Cu(II), while the small peak of 932.7eV is related to the presence of Cu(I) or Cu(0) species.
[0148] like Figure 3 As shown in (a), with the increase of the carbon chain of the alkyl substituent on the nitrogen atom of 2-pyrrolidone, the binding energy of Cu(II) in the catalyst gradually decreases, indicating that with the increase of the alkyl chain length on the nitrogen atom in the 2-pyrrolidone ligand, the electron donating ability of the ligand gradually increases. During the preparation and characterization of the catalyst, Cu(II) may be reduced to Cu(I) or Cu(0), so there are also some Cu(I) or Cu(0) species on the catalyst surface before the reaction.
[0149] Figure 3 (c) and Figure 3 (d) shows the XAES spectrum of the catalyst, and the binding energy difference between Cu(I) and Cu(0) can be distinguished by the Cu LMM Auger spectrum. A transition state peak associated with Cu is observed at 910.5 eV, while Cu(0), Cu(II), and Cu(I) show peaks around 918.6 eV and 915.5 eV, respectively.
[0150] from Figure 3(b) and 3(d) show that the ratio of Cu(II) / Cu(I) in the Cu-Lx / AC catalyst after the reaction is significantly reduced, indicating that the Cu(II) species in the catalyst is reduced to Cu(I) or Cu(0) by acetylene during the reaction. As the length of the alkyl chain on the nitrogen atom of the 2-pyrrolidone ligand increases, the relative content of the low-valent Cu active component increases. In addition, the binding energy of Cu(II) in the Cu-NEP / AC catalyst shows a relatively negative BE shift, indicating that the NEP ligand helps to reduce Cu(II) to Cu(I). The binding energy of Cu(I) shows a relatively positive BE shift, indicating that NEP can inhibit the reduction of Cu(I) to Cu(0), which indicates that the addition of the ligand can stabilize the valence state of Cu ions. XPS results show that the NEP ligand promotes the reduction of Cu(II) to Cu(I) and inhibits the reduction of Cu(I) to Cu(0).
[0151] Example 18.
[0152] X-ray diffraction (XRD) was performed using a D8ADVANCE instrument from Bruker, Germany, to record XRD data for analyzing the crystal structure of the catalyst. The radiation source used was Cu Kα, the operating current was 40 mA, the voltage was 40 mV, and the 2θ angle range was between 10° and 90°.
[0153] In order to further study the effect of pyrrolidone ligands on Cu-based catalysts and gain a deeper understanding of the potential active substances of Cu-based catalysts, XRD characterization was performed on the catalysts before and after the reaction (the reaction was carried out using the method of Example 13). Figure 4 As shown in (a), Cu / AC catalyst before reaction, CuCl can be observed at 2θ values of 16.29°, 22°, 28.95°, and 34.01°. 2 (H 2 O) 2 (JCPDS 72-0572). This is because the Cu species aggregated during the preparation process and interacted with the catalyst surface to form CuCl 2 (H 2 O) 2 For the Cu-Lx (L1, L2, L3, L4, L5 and L6) / AC catalysts before the reaction, no obvious Cu crystalline diffraction peaks were observed except for the amorphous carbon diffraction peaks of activated carbon. This indicates that the addition of pyrrolidone ligands during the catalyst preparation process can improve the dispersibility of the Cu component in the catalyst.
[0154] Figure 4(b) shows the XRD spectra of Cu / AC, Cu-Lx (L1, L2, L3, L4, L5 and L6) / AC catalysts after 20 hours of reaction. It can be observed that in the Cu-Lx (L1, L2, L3, L4, L5 and L6) / AC catalysts, except for the amorphous diffraction peak of carbon (JCPDS 75-1621), no obvious Cu and pyrrolidone ligand reflection peaks were found. This result shows that the particle size of Cu species is less than 4nm or exists in an amorphous form in the catalyst. For the Cu / AC catalyst after the reaction, CuCl (JCPDS 06-0344) diffraction peaks can be observed at 2θ values of 28.49°, 32.92°, 47.43° and 56.28°. The XRD test results show that the introduction of an appropriate amount of 2-pyrrolidone ligands can inhibit the formation of CuCl and promote the dispersion of Cu on activated carbon, which is consistent with the catalyst activity test results.
[0155] Example 19.
[0156] The redox of the catalyst is a key factor in the acetylene dimerization reaction. In order to study the effect of the ligand on the reduction of the catalyst, H 2 -TPR characteristic analysis. H of the catalyst prepared in the embodiment of the present invention 2 -TPR curve is as follows Figure 5 shown.
[0157] The reducibility of the active components in the catalyst was tested using an ASPA2720 instrument from Micromeritics, USA, using a hydrogen programmed temperature reduction (H 2 Temperature Programmed Reduction, H 2 First, 0.1 g of the sample (catalysts of Example 1 and Example 5) was heated to 40 °C in N 2 The sample was treated in a 4% sodium-ion gas atmosphere for 60 min to remove impurities. After the sample cooled, it was then heated at a flow rate of 80 mL min -1 10% H 2 / Ar reducing atmosphere, at 10℃ min -1 The temperature was increased from room temperature to 900 °C at a heating rate of , and the TCD signal changes were recorded.
[0158] Figure 5Figure 2 is the TPR curve of Cu / AC and Cu-NEP / AC catalysts before and after the reaction. Three obvious characteristic reduction peaks can be observed in the TPR curves of all catalysts. The peak appearing at about 340°C represents the characteristic reduction peak of Cu(II), while the peak appearing at about 400°C represents the characteristic reduction peak of Cu(I). The characteristic reduction peak observed in the region of about 600°C is related to the number of oxygen-containing groups on the AC surface. The characteristic reduction peak of Cu(II) in the Cu / AC catalyst appears at about 328.4°C, while the characteristic reduction peak of Cu(II) in the Cu-NEP / AC catalyst appears at about 340.6°C.
[0159] Compared with the Cu / AC catalyst, the reduction temperature of Cu(II) in the Cu-NEP / AC catalyst decreased by 12.2°C, indicating that the NEP ligand can promote the reduction of Cu(II) to Cu(I) in the Cu-based catalyst and increase the reducibility of the Cu(II) species in the catalyst. The characteristic reduction peak of Cu(I) in the Cu / AC catalyst appears at about 400.1°C, while the characteristic reduction peak of Cu(I) in the Cu-NEP / AC catalyst appears at about 412.6°C. Compared with the Cu / AC catalyst, the reduction temperature of Cu(I) in the Cu-NEP / AC catalyst increased by 12.5°C, indicating that the NEP ligand inhibited the reduction process of Cu(I) to Cu(0).
[0160] From the TPR curve of the catalyst, it can be observed that the reduction peak area of Cu(II) and Cu(I) of the Cu / AC catalyst after the reaction is significantly reduced, while there is no significant difference in the Cu-NEP / AC catalyst. Therefore, compared with the Cu / AC catalyst, Cu-NEP / AC has better catalytic performance. This is because the NEP ligand in Cu-NEP / AC promotes the reduction of Cu(II) to Cu(I) and inhibits the further reduction of Cu(I) to Cu(0). The TPR test results show that the NEP ligand can stabilize the valence state of the Cu species in the catalysis to a certain extent, which is consistent with the XPS results.
[0161] Example 20.
[0162] The catalyst samples were analyzed by thermogravimetric-differential scanning calorimetry (TG-DSC) (under air atmosphere) using a synchronous thermal analyzer (TATGA5500, USA). After the baseline was stabilized, the temperature was raised from 25°C to 800°C (10°C / min) to obtain the weight loss data of the catalyst. The carbon deposition of Cu / AC and Cu-NEP / AC catalysts (catalysts of Example 1 and Example 5) before and after the reaction was studied by thermogravimetric (TG). The results are shown in Figure 2. Figure 5 shown.
[0163] Figure 6(a) is the TG and DTG curves of the Cu / AC catalyst before and after the reaction. The weight loss in the range of 151-370°C directly reflects the degree of coking deposition on the surface of the Cu / AC catalyst. The amount of carbon deposited on the surface of the Cu / AC catalyst after the reaction is 15.35%.
[0164] like Figure 6 As shown in (b), the Cu-NEP / AC catalyst before and after the reaction showed three different weight loss stages. Before 126°C, the weight decreased slightly, which was caused by the desorption of water molecules and other weakly adsorbed substances on the catalyst surface. A slow weight reduction occurred in the temperature range of 100-370°C, which was caused by the combustion of acetylene polymers and carbon deposits on the catalyst. When the temperature exceeded 370°C, the combustion of the activated carbon support itself caused the catalyst to lose weight rapidly.
[0165] Therefore, the carbon deposition content was determined by comparing the mass change of the Cu-NEP / AC catalyst in the corresponding temperature range before and after the reaction. The carbon deposition analysis of the catalyst showed that the surface carbon deposition of the Cu / AC catalyst was about 15.35%, while the surface carbon deposition of the Cu-NEP / AC catalyst was only about 4.92%. The TG results showed that the introduction of the NEP ligand effectively inhibited the carbon deposition during the gas-solid acetylene dimerization reaction and improved the stability of the catalyst.
[0166] Example 21.
[0167] TEM images of the catalysts were taken using an electron microscope (Titan G260-300). Finally, the TEM images were analyzed using nano-measurement software to obtain particle size data.
[0168] Transmission electron microscopy (TEM) was used to characterize the morphology of the catalyst. Figure 7 In (a), it can be observed that there are many unevenly dispersed Cu nanoparticles on the surface of Cu / AC before the reaction. These nanoparticles are irregular in shape. According to the TEM results, the particle size distribution of Cu nanoparticles on Cu / AC is 5-9nm, and the average particle size is 6.7nm. Figure 7 As shown in (b), the size of the nanoparticles on the Cu-NEP / AC catalyst before the reaction also ranges from 0.8 to 1.6 nm and is evenly distributed on the surface of the carrier. The average size of the nanoparticles is 1.2 nm. Figure 7 No black particles are seen in (b), which indicates that the NEP ligand introduced during the catalyst preparation process can effectively inhibit the aggregation of Cu species.
[0169] In order to verify the above conclusions, TEM element scanning was performed on the Cu / AC and Cu-NEP / AC catalysts (catalysts of Examples 1 and 5) before and after the reaction. Figure 7 (a) and 7(b), it can be found that the Cu element in the Cu / AC catalyst is in an aggregated state, while the Cu element in the Cu-NEP / AC catalyst is more dispersed. In the Cu / AC and Cu-NEP / AC catalysts, the oxygen and chlorine elements exist in a highly dispersed manner. The N element detected in the Cu-NEP / AC catalyst comes from the NEP ligand, and its high dispersion indicates that the NEP ligand is well dispersed on the activated carbon. Therefore, the NEP ligand introduced during the catalyst preparation process effectively promotes the high dispersion of Cu species on the activated carbon.
[0170] like Figure 7 As shown in (c) and 7(d), the catalyst showed obvious agglomeration after the reaction. In the Cu / AC catalyst, Cu was severely aggregated, while in the Cu-NEP / AC catalyst it was in a better dispersed state. During the reaction, the average particle size of the Cu / AC catalyst increased from 6.87nm to 89.36nm. However, after the introduction of the NEP ligand, the average particle size of the Cu / AC catalyst after the reaction only increased from 1.6nm to 4.6nm, which shows that the addition of NEP ligand can effectively inhibit the agglomeration of Cu species in the catalyst during the reaction. This plays a key role in heterogeneous catalysis. Figure 7 From the TEM element scans of (c) and 7(d), it can be seen that the Cu element in the Cu / AC catalyst showed obvious aggregation, while the Cu element in the Cu-NEP / AC catalyst only had slight aggregation. In the Cu / AC and Cu-NEP / AC catalysts after the reaction, the O element and the Cl element also showed aggregation, and the aggregation degree was highly consistent with that of the Cu species in their respective catalysts. This indicates that the agglomerates may be a mixture of Cu, O, and Cl. It is worth noting that the distribution of N elements in the Cu-NEP / AC catalyst did not change before and after the reaction, which indicates that the agglomerates do not contain NEP ligands. TEM results show that the introduction of an appropriate amount of NEP ligands can not only promote the uniform dispersion of Cu active components during the preparation of Cu-based catalysts, but also effectively inhibit the aggregation of Cu species in the gas-solid acetylene dimerization reaction.
[0171] In summary, compared with the large amount of organic solvents and co-catalysts used in the previous preparation of catalysts, the present invention uses water as solvent and NEP as ligand to prepare Cu-NEP / AC catalyst, which has the characteristics of low price and green environmental protection. Therefore, the present invention provides a new method for synthesizing vinyl acetylene that is efficient, stable, environmentally friendly and economical.
[0172] Example 22.
[0173] Transmission mode (fluorescence mode) and X-ray absorption spectroscopy (XAS) observations of the X-edge were performed using the Advanced Photon Source on the 12-BM beamline at Argonne National Laboratory. X-ray absorption fine structure (XAFS) spectra of the Cu K edge were measured. Athena and Artemis software were used to examine the XANES and EXAFS data. Data reduction, data analysis, and EXAFS fitting were performed using the Athena and Artemis software packages.
[0174] The electronic properties and coordination structure of Cu in Cu-Lx (L1, L2, L3, L4, L5 and L6) ligand catalysts were analyzed by changes in X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectra. 2 O, CuO, Cu(OH) 2 , CuCl 2 , Cu foil, and the catalysts of Examples 3-8.
[0175] Result: Passed Cu-L1 / AC, Cu-L2 / AC, Cu-L3 / AC, Cu-L4 / AC, Cu-L5 / AC, Cu-L6 / AC, Cu 2 O, CuO, Cu(OH) 2 , CuCl 2 From the XANES spectra of Cu foil and Cu K-edge, it can be seen that the spectra of all Cu-based ligand catalysts show the characteristic of Cu(II) species (peak at 8977.5 eV), the weak front peak is caused by the dipole-forbidden Cu(II) 1s→3d electronic transition, the shoulder peak at 8985 eV (at C) and the peak at 9000 eV (at D) correspond to the Cu(II) 1s→4p electronic transition, and the small shoulder peak at 8983.3 eV (at B) is caused by the Cu(I) 1s→4p conversion. Therefore, from the XANES spectra of Cu K-edge, it can be seen that the absorption edge of Cu-L1 / AC, Cu-L2 / AC, Cu-L3 / AC, Cu-L4 / AC, Cu-L5 / AC and Cu-L6 / AC catalysts is located at Cufoil, Cu 2 O and CuO, Cu(OH) 2 , CuCl 2 This indicates that the average valence state of the Cu species in the catalyst is between (I) and (II), indicating the coexistence of Cu(II) and Cu(I). The absorption edge of the Cu-L6 / AC catalyst is closer to Cu 2O and Cufoil, indicating that more Cu(II) species were reduced to Cu(I) or Cu(0) species during the catalyst preparation process. Compared with Cu-L6 / AC, the absorption edge of Cu-L1 / AC catalyst shifted to higher energy CuO, Cu(OH) 2 and CuCl 2 The absorption edge of Cu-L1 / AC catalyst indicates that the number of Cu atoms in the Cu(II) state is greater. It is also found that with the increase of the chain length of the substituent on the nitrogen atom of the 2-pyrrolidone ligand, the absorption edge of the Cu-based ligand catalyst moves toward a lower energy direction.
[0176] In addition, the oscillation curves of Cu-L1 / AC, Cu-L2 / AC, Cu-L3 / AC, Cu-L4 / AC, Cu-L5 / AC and Cu-L6 / AC catalysts are similar to those of Cu 2 O and Cu foil oscillation curves are different, but similar to CuCl 2 and Cu(OH) 2 The oscillation curves of the catalysts are well matched. This further proves their similar central atomic coordination environment. Then the R space experimental results of Cu Kedge EXAFS were curve fitted to quantitatively analyze the local environment differences of each catalyst, including the type of coordinated atoms, bond length, coordination number, etc.
[0177] According to the results of quantitative fitting, and comparing Cu foil, Cu 2 O、Cu(OH) 2 and CuCl 2 Standard samples, found that the sample peak contains Cu-N / O and Cu-Cl signals. The peak at (without phase correction) is attributed to the scattering path of the Cu-O bond. The peak at (without phase correction) is attributed to the scattering path of the Cu-Cl bond.
[0178] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.
Claims
1. A catalyst for acetylene dimerization reaction, characterized in that: include: Main catalyst, ligand, carrier; The main catalyst is cupric chloride; the ligand is 1-ethyl-2-pyrrolidone; and the carrier is coconut shell activated carbon.
2. The catalyst according to claim 1, characterized in that The molar ratio of the main catalyst to the ligand is 1:0.5-2.
3. The catalyst according to claim 1, characterized in that The mass ratio of the copper element to the carrier in the main catalyst is 5-20:
100.
4. The catalyst according to claim 1, characterized in that The coconut shell activated carbon is 60-80 mesh coconut shell activated carbon.
5. The method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) After the main catalyst is completely dissolved in water, the ligand is added dropwise at 20-50°C and stirred to allow it to fully coordinate to obtain a complex solution; (2) adding a carrier to the complex solution, stirring to load the complex on the carrier, and drying to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: In the step (1), stirring is performed for 20-40 minutes to allow the main catalyst and the ligand to be fully coordinated.
7. The preparation method according to claim 5, characterized in that: In the step (2), the drying process is: drying at 60-90°C for 4-12h, and then drying at 90-120°C for 4-12h.
8. The preparation method according to claim 5, characterized in that: In the steps (1) and (2), the stirring speed is 300-700 rpm.
9. Use of the catalyst according to claim 1 in acetylene dimerization reaction, characterized in that: The catalyst according to any one of claims 1 to 4 is added into a reactor, and then acetylene is introduced into the reactor to cause a dimerization reaction to generate vinyl acetylene.
10. The preparation method according to claim 9, characterized in that: The reaction temperature in the reactor is 90-110°C, and the acetylene space velocity is 100-140h -1 .